PR Prolongation predicts inadequate resynchronization with biventricular pacing in left bundle branch block. Issue 11 (22nd September 2019) - Atwater, Brett D.; Emerek, Kasper; Sørensen, Peter L.; Hansen, Steen M.; Loring, Zak; Graff, Claus; Polcwiartek, Christoffer; Kisslo, Joseph; Søgaard, Peter; Friedman, Daniel J.
Abstract: Background: PR interval prolongation is associated with poor outcome after cardiac resynchronization therapy (CRT) among patients with left bundle branch block (LBBB) but the mechanisms are unknown. We investigated clinical outcomes, electrocardiogram (ECG), and echocardiogram changes after CRT by PR interval. Methods: This is a retrospective study of CRT recipients with a baseline ejection fraction ≤35% and ECG showing sinus rhythm and LBBB. Patients were stratified by baseline PR interval quartile and the primary combined endpoint was time to heart transplantation, left ventricular assist device (LVAD) implantation, or death. ECG, echocardiogram, and clinical variables were compared to identify mechanisms for observed differences in outcomes. Results: Of 291 eligible patients, the mean age was 65 years, 60% were male, and 19% had prior atrial fibrillation. Patients with PR prolongation (quartile 4, PR > 200 ms) more frequently had a history of atrial fibrillation, coronary artery bypass graft surgery, prior implantable cardioverter defibrillator implantation, and use of amiodarone than patients in PR quartiles 1‐3. A PR > 200ms was associated with an adjusted hazard ratio of 1.7 (95% CI: 1.1‐2.5) for the primary endpoint. Patients with PR > 200 ms had less reduction in QRS duration and QRS area after CRT while having more increase in QT and QTc intervals than patients with PR ≤ 200 ms. No major differences were observed in echocardiography by baseline PR interval quartiles. Conclusions: PR prolongation predicts shorter survival free of heart transplantation or LVAD implantation in patients with LBBB. This may be due to inadequate ventricular resynchronization.